A cidade que educa : a construção da identidade social dos trabalhadores da cidade-empresa de Volta Redonda (1940-1973) - Medeiros, Simone Alves de (2007)
The policy made effective during the ESTADO NOVO (1937- 1945), introduced by Getúlio Vargas dogmatically, without significant social mobilization, represented an alliance between civil and military burocracy with industrila burgership, that the primordial interest was to promote the industrialization in the country. So, the greater preocupation was the organization of the industrila support, replacing the impottations. That policy intended to make the new type of worker that could atendthe economics, social and ideologics demandsof the capitalism system of prodution. In this context, were created the COMPANHIA SIDERÚRGICA NACIONAL(CSN) located in Volta Redonda, in 1941, the ESCOLA PROFISSIONAL DA CSN(1943), then ESCOLA TÉCNICA PANDIÁ CALÓGERAS(ETPC), in 1954 and its labor city, constructed jointly the factory. Vargas considered the CSN, ETPC and its city models of work and progress for the nation, because making an efficient, capable and disciplinated worker. The idealization and construction of cities as an extension of the company, in that case, the company-town, turn to be an efficient instrument of domination, because gave contribution in the process of adaptation of the worker to the identification with the conception of a captalism world, focusing the education, domination and subordination of the labor force in the fields of production and reproduction. The urban plan of the company-town of Volta Redonda revealed the central position of CSN in concerning to its siderurgiv family and repeated in its urban structure the functional hierarchyof the factory, building divided places, based on the functional category and level of wages, especialy, its branches with an inequal policy producing inequality. The City of Steel taught and form the most of its siderurgic family, tracing their lives, when affected directly the way their lives should go, building an social identity linked with the company.